Physico-Chemical Assessment of the Jalaur River System, Iloilo, Philippines - Borlongan, Ilda G.; Golez, Nelson V.; Lorque, Felizardo (Silliman Journal, 2022)
5IF +BMBVS3JWFS4ZTUFNXBT TUVEJFEGPSUIFRVBMJUZPGJUTXBUFS CFDBVTFXBUFSRVBMJUZJTBTJHOJmDBOUBOEQPXFSGVMEFUFSNJOBOUPG UIFIFBMUIPGBRVBUJDFDPTZTUFNT5IJTTUVEZBJNFEBUJOWFTUJHBUJOH the physico-chemical parameters, nutrient load, heavy metal concentrations and pesticide residues of the Jalaur River system. One of the purposes of this study was to develop a database on the seasonal changes in these river characteristics. 2VBOUJUBUJWFTBNQMFTPGXBUFS TFEJNFOUT BMHBFBOEmTIXFSF collected and analyzed during the rainy season (July-September BOEUIFESZTFBTPO +BOVBSZ.BSDI GSPNmWFTBNQMJOH stations representing upstream, midstream and downstream TFDUJPOTPGUIFLJMPNFUFSMPOHSJWFS#BTFEPOUIFXBUFSRVBMJUZ TUBOEBSE BOEXBUFS DMBTTJmDBUJPO BEPQUFECZ%&/3 UIF +BMBVS 3JWFSTUSFUDIDBOCFDMBTTJmFEBTDMBTT$BOE%$MBTT$XBUFSJTGPSQSPQBHBUJPOBOEHSPXUIPGBRVBUJDSFTPVSDFTXIJMFDMBTT% water is for agriculture, irrigation, livestock watering, and industrial cooling and processing. The detected levels of metal contamination, mainly Cr, and Pb, in sediments of Jalaur River were found to exceed the geochemical background or threshold levels. Lead and chromium XFSFBMTPEFUFDUFEJOmMBNFOUPVTBMHBF MVNPU Azolla, and tilapia (Oreochromis niloticus) sampled at Moroboro sampling site. No organochlorines, organophosphates, carbamates, and pyrethroids pesticides were detected at the detection limit of the analyses for both water and sediment samples. 5IFEFUFSJPSBUJPOJOUIFQIZTJDPDIFNJDBMRVBMJUZBOE SJTFJO the nutrient levels observed in this study is alarming, and periodic NPOJUPSJOH BOE QSFWFOUJWF NFBTVSFT BSF SFRVJSFE UP TBWF UIF BRVBUJD TZTUFNGSPN FVUSPQIJDBUJPO )FBWZNFUBM DPOUBNJOBUJPO PGCPUUPNTFEJNFOUT BMHBFBOEmTITBNQMFTJTBMTPBDBVTFGPS alarm because these heavy metals pose threats to human health. 5IFmOEJOHTIBWFJNQPSUBOUJNQMJDBUJPOTGPSUIFEFWFMPQNFOUPG effective water management strategies and as guide to remediation efforts for the Jalaur River system.